2010
DOI: 10.1542/peds.2009-1653
|View full text |Cite
|
Sign up to set email alerts
|

Measles Outbreak in a Highly Vaccinated Population, San Diego, 2008: Role of the Intentionally Undervaccinated

Abstract: Despite high community vaccination coverage, measles outbreaks can occur among clusters of intentionally undervaccinated children, at major cost to public health agencies, medical systems, and families. Rising rates of intentional undervaccination can undermine measles elimination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
117
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 245 publications
(131 citation statements)
references
References 18 publications
0
117
0
2
Order By: Relevance
“…Much can be learned from measles outbreaks, especially in describing pockets of under-immunized people that may require targeted preventive efforts, 27 and in documenting response strategies that were successful in limiting measles spread. Data from elimination settings indicate that the characteristics of unvaccinated populations are diverse; they may be faith-based groups, 12 ethnic subpopulations, 14 , 28 and certain age-cohorts 29 or members of a socioeconomic strata 30 that experienced lower immunization coverage historically. As such, preventive and response measures should be tailored to each population to be effective.…”
Section: Outbreak Response Activitiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Much can be learned from measles outbreaks, especially in describing pockets of under-immunized people that may require targeted preventive efforts, 27 and in documenting response strategies that were successful in limiting measles spread. Data from elimination settings indicate that the characteristics of unvaccinated populations are diverse; they may be faith-based groups, 12 ethnic subpopulations, 14 , 28 and certain age-cohorts 29 or members of a socioeconomic strata 30 that experienced lower immunization coverage historically. As such, preventive and response measures should be tailored to each population to be effective.…”
Section: Outbreak Response Activitiesmentioning
confidence: 99%
“…Costs incurred by the public health sector during the response, or even a full economic evaluation, are also of interest. 30-32 Finally, data from social media and search engines have been used to measure public measles vaccine confidence and the effectiveness of communication strategies during measles outbreaks, 23-26 and might also be helpful for the early detection of outbreaks and to monitor disease spread, as has been done for other pathogens. 21 , 22 Findings from these analyses should be disseminated to relevant stakeholders, e.g., frontline clinicians involved in the response, state or national public health authorities responsible for identifying and closing immunity gaps, and policy makers.…”
Section: Outbreak Response Activitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have characterized unvaccinated children belonging to families intentionally refusing vaccines with similar demographic characteristics. 9,[26][27][28][29][30] There are several reasons for parents claiming non-medical exemptions to routine childhood immunizations for school entry. A case-control study of unvaccinated children claiming nonmedical exemption reported significantly lower perceived vaccine safety (61% vs. 15%) and efficacy (54% vs. 17%), lower perceived disease susceptibility (58% vs. 15%) and severity (51% vs. 18%), and low trust in the government (40% vs. 23%) compared with vaccinated children.…”
Section: Perception Of Vaccine Exemptors and Hesitant Parentsmentioning
confidence: 99%